Patterns of Polar Domains in a Spatiotemporal Model of Interacting Polarities - Aliee, Maryam; Boudaoud, Arezki (Physical Review Letters, 2019)
Polarity fields are known to exhibit long distance patterns, in both physical and biological systems. The mechanisms behind such patterns are poorly understood. Here, we describe the dynamics of polarity fields using an original physical model that generalizes classical spin models on a lattice by incorporating effective transport of polarity molecules between neighboring sites. We account for an external field and for ferromagnetic interactions between sites and prescribe the time evolution of the system using two distinct dissipative classes for nonconserved and conserved variables representing polarity orientation and magnitude, respectively. We observe two main types of steady-state configurations-disordered configurations and patterns of highly polar spots surrounded by regions with low polarity-and we characterize patterns and transitions between configurations. Our results may provide alternative pattern-generating mechanisms for materials endowed with polarity fields.
CRIS-Team WoS Importer:2019-07-26

Semi-Automatic Cell Correspondence Analysis Using Iterative Point Cloud Registration - Chen, Shuqing; Gehrer, Simone; Kaliman, Sara; Ravikumar, Nishant; Becit, Abdurrahman; Aliee, Maryam; Dudziak, Diana; Merkel, Rudolf; Smith, Ana-Suncana; Maier, Andreas (Bildverarbeitung für die Medizin 2019. Informatik aktuell., 2019)